Preparation and Characterization of Hydroxyapatite/Poly(Ethylene Oxide) Nanocomposite Nanofibers - Zhang, Y.Z.; Li, Q.; Yi, B.C.; Su, B.; EI-Turki, A. (Journal of Composites and Biodegradable Polymers, 2019)
Developing nanofillers incorporated polymer nanofibers (i.e., nanocomposite nanofibers) is an effective approach to achieve functionality and efficiency in nanomaterials applications. In this paper, spindle- or needle-shaped hydroxyapatite (HA) nanoparticles with sizes of ca. 100 x 30 nm were synthesized by a wet chemical method. HA-incorporated poly(ethylene oxide) (PEO) nanocomposite nanofibers were then successfully fabricated via electrospinning aqueous solutions of HA/PEO blends with varied HA contents. Scanning electron microscope and transmission electron microscope observations indicated that if higher HA loadings (e.g., 30%, 50%) were involved, the resultant fiber morphology would be affected by occurring HA aggregates along the fiber axis. The HA nanoparticles were found to aggregate discretely forming raisin-like morphology with their long axis in alignment with the fiber direction. XRD and FTIR results provide evidence of molecular interactions between the nanocrystal HA and PEO, likely because of the formation of hydrogen bondings. With this, it is believed that further development of current HA/PEO nanocomposite nanofibers, biologically mimicking the basic building blocks of the natural bone, may lead to potential applications in repairing hard tissues like bone as well as in developing efficient optoelectronic nanodevices.